The Taking Action Guide to Building Coherence in Schools, Districts, and Systems - Fullan, Michael; Quinn, Joanne; Adam, Eleanor Ms (Corwin, 2016)
Get there faster: Your road map to smart, sustainable change! Taking Action is a hands-on guide to the groundbreaking book, Coherence: The Right Drivers in Action for Schools, Districts and Systems, providing step-by-step protocols to help foster deep coherence for maximum student learning-all within a reasonably short time frame. You'll develop: Deeper understanding of The Coherence Framework A 100-Day Coherence Plan Leadership, capacity, and coalition-building skills Systems and tools to assess your organization Includes video links, print resources, case studies, and diagnostic and p.